XMM-Newton view of the N 206 superbubble in the Large Magellanic Cloud - Kavanagh, Patrick; Sasaki, Manami; Points, Sean (Astronomy & Astrophysics, 2012)
Conclusions. Using the high-sensitivity X-ray data from XMM-Newton and optical data from the Magellanic Cloud Emission Line Survey has allowed us to better understand the physical properties of the N 206 superbubble and address some key questions of superbubble evolution.
Keywords: Magellanic Clouds; ISM: bubbles; evolution; HII regions; X-rays: ISM